Instructional leadership and deep learning in the implementation of the student center learning: a case study of a junior high school in indonesia - Septi Emilya; Manap Somantri; Muhammad Kristiawan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study aims to describe the principal’s instructional leadership in accelerating deep learning in the implementation of the independent curriculum at Junior Hight School number 20 bengkulu city which includes the role of the principal, the principal’s strategy, the obstacles faced, the impact and the influence of the principal’s instructional leadership on the quality of the implementation of deep learning on the implementation of the independent curriculum at Junior High School number 20 bengkulu city. the method used is descriptive qualitative with interview, observation, and documentation techniques. data analysis was carried out using the interactive model of miles and huberman which consists of data reduction, data presentation, and data verification. the results of the study are 1). The school principal succeeded in directing teachers to implement deep learning through clear instructional policies and school programs that support Student Center Learning. 2) Principal guidance, supervision, and feedback accelerate the application of deep learning and improve the quality of planning and teacher learning practices. 3) The implementation of instructional leadership still faces obstacles, especially teacher readiness, administrative burden, limited facilities, and not optimal training and external support. 4) instructional leadership has an impact on improving teacher professionalism in designing project-based learning, authentic assessment, and higher-level thinking activities. 5). Principal leadership is a determining factor for the success of deep learning, indicated by increased engagement, critical thinking skills, and the quality of student learning outcomes. Its contribution provides an empirical reference for school principals and policy makers in strengthening the role of instructional leadership to improve the quality of deep learning.